Conflict Transformation and Asymmetric Conflicts: A Critique of the Failed Turkish-Kurdish Peace Process - Baser, Bahar (Terrorism and political violence, 2021)
In this article, we examine the dynamics of the Kurdish-Turkish peace process that collapsed in the summer of 2015. The negotiations began when the conflict reached a certain level of ripeness, one that made it possible for both sides to entertain the possibility of compromise on various taboo issues. However, in the face of both domestic and international developments, the process came to an abrupt halt. This article argues that the main reason the process stalled was because it was built from the start around the idea of “resolution” rather than “transformation,” a concept better suited to responding to highly fluid asymmetric conflicts.